2018
DOI: 10.31033/ijemr.8.3.17
|View full text |Cite
|
Sign up to set email alerts
|

Physiochemical Properties and Meat Quality Parameters of Wild Boar Meat: A Review

Abstract: Wild boar meat has well balanced with nutrients and comprised with unique sensory attributes and meat quality parameters, however, limited information and studies have been performed on nutritional quality and meat quality parameters. The proximate composition of wild boar meat, mainly protein and fat contents were ranged at 21.6-24.11% and 2.27-2.62% respectively. The composition of fatty acids in wild boar has obtained higher values for unsaturated fatty acids particularly mono unsaturated fatty acids; nonet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
(20 reference statements)
0
2
1
Order By: Relevance
“…The meat of wild boar is found to contain more protein and less fat than the meat of a domestic pig. The result on a crude protein of the wild boar crosses in the current study was found lower compared to its parents, 22.79±0.78 in Duroc (Choi et al, 2014) and 21.81 to 22.92 in wild boar (Kumar, 2018). The crude fat in the flesh of male and female boars was 4.42±0.07% and 5.47±0.07% respectively.…”
Section: Proximate Analysis Of Meat Componentscontrasting
confidence: 61%
See 1 more Smart Citation
“…The meat of wild boar is found to contain more protein and less fat than the meat of a domestic pig. The result on a crude protein of the wild boar crosses in the current study was found lower compared to its parents, 22.79±0.78 in Duroc (Choi et al, 2014) and 21.81 to 22.92 in wild boar (Kumar, 2018). The crude fat in the flesh of male and female boars was 4.42±0.07% and 5.47±0.07% respectively.…”
Section: Proximate Analysis Of Meat Componentscontrasting
confidence: 61%
“…The crude fat in the flesh of male and female boars was 4.42±0.07% and 5.47±0.07% respectively. Past studies showed that the crude fat content is higher in crossbreeds than in Duroc and wild boar (Choi et al, 2014;Kumar, 2018). The results of dry matter, total ash, iron, calcium, and phosphorous contents in the current study were 27.47±0.72%, 0.99±0.03%, 2.56±0.22 31.17±3.69 177.36±4.73 respectively (Table 2) which were comparable to the findings as reported by various researchers (Anwer et al, 2013;Choi et al, 2014;Kumar, 2018).…”
Section: Proximate Analysis Of Meat Componentsmentioning
confidence: 99%
“…Unlike predatory hunting in Brazil, the production of peccary (Tayassu pecari, Link, 1975) offers new perspectives for the meat, skin and leather industries. Peccary meat is greatly appreciated by national and international consumers because of its quality and sensory characteristics; however, studies on this species are still scarce (Kumar, 2018). The skin and leather used by foreign industries serve as a specific niche market for the production of luxury goods (Sowls, 1984;Fang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%